Nanosuspension Innovations: Expanding Horizons in Drug Delivery Techniques - Shery Jacob; Fathima Sheik Kather; Sai H. S. Boddu; Mahesh Attimarad; Anroop B. Nair (Pharmaceutics)
Nanosuspensions (NS), with their submicron particle sizes and unique physicochemical properties, provide a versatile solution for enhancing the administration of medications that are not highly soluble in water or lipids. This review highlights recent advancements, future prospects, and challenges in NS-based drug delivery, particularly for oral, ocular, transdermal, pulmonary, and parenteral routes. The conversion of oral NS into powders, pellets, granules, tablets, and capsules, and their incorporation into film dosage forms to address stability concerns is thoroughly reviewed. This article summarizes key stabilizers, polymers, surfactants, and excipients used in NS formulations, along with ongoing clinical trials and recent patents. Furthermore, a comprehensive analysis of various methods for NS preparation is provided. This article also explores various in vitro and in vivo characterization techniques, as well as scale-down technologies and bottom-up methods for NS preparation. Selected examples of commercial NS drug products are discussed. Rapid advances in the field of NS could resolve issues related to permeability-limited absorption and hepatic first-pass metabolism, offering promise for medications based on proteins and peptides. The evolution of novel stabilizers is essential to overcome the current limitations in NS formulations, enhancing their stability, bioavailability, targeting ability, and safety profile, which ultimately accelerates their clinical application and commercialization.